2017
DOI: 10.1109/tthz.2017.2723803
|View full text |Cite
|
Sign up to set email alerts
|

Specific Capacitance Dependence on the Specific Resistance in Nb/Al–AlOx/Nb Tunnel Junctions

Abstract: The junction specific capacitance (Cs) is an essential parameter in designing tuning circuitry for Superconductor-Insulator-Superconductor (SIS) mixers. However, our knowledge of the junction capacitance only relies on the few available empirically obtained Cs vs. specific normal resistance (RnA) relations, which are inconsistent especially at low RnA values, RnA < 40 Ω.µm 2. In this paper, we report the Nb/Al-AlOx/Nb SIS junction capacitance data from our recently presented direct microwave (4 GHz) measuremen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…We however found that the measurement uncertainty of the R n C varies depending on the junction area and is between just 62% to 611.2% for the largest and smallest junctions among all the batches, respectively. 27 Therefore, the scatter of the area-independent R n C product emphasizes that the scatter also has intrinsic origins, e.g., the barrier thickness non-uniformity. In order to show this, the tunnel barrier thickness distribution needs to be found.…”
Section: -5mentioning
confidence: 99%
“…We however found that the measurement uncertainty of the R n C varies depending on the junction area and is between just 62% to 611.2% for the largest and smallest junctions among all the batches, respectively. 27 Therefore, the scatter of the area-independent R n C product emphasizes that the scatter also has intrinsic origins, e.g., the barrier thickness non-uniformity. In order to show this, the tunnel barrier thickness distribution needs to be found.…”
Section: -5mentioning
confidence: 99%
“…[3,4]. In order to determine the specific capacitance (C s ) of the IJJ at superconducting state, the most used experimental method is direct microwave experiment [5]. In this context, the determination of the specific capacitance of the superconducting sample has a crucial importance in order to understand the superconducting mechanism.…”
Section: Introductionmentioning
confidence: 99%